New convergence analysis of coverage control on a circle subject to unknown but bounded measurement errors - Song, Cheng; Fan, Yuan; Xu, Shengyuan (Automatica (Oxford), 2022)
The coverage problem for heterogeneous mobile sensor networks subject to unknown but bounded position measurement errors on a circle is reconsidered, where the sensors’ spatial order on the circle is required to be always preserved. In the existing results, convergence of the proposed coverage control law relies on the assumption that a function of neighboring sensors’ measurement errors achieves its maximum in finite time, which may not be satisfied in real-world applications. The assumption is removed in this technical communique by using a new convergence analysis approach. Another benefit of the proposed approach is a less conservative upper bound on the limit of the coverage cost function.